The The Role of Diplomatic Conferences in the Development of Legislative Mechanisms in International Law - Hama Rashid Saed , Raqeeb (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
The current study examines the influence of three vital diplomatic conferences, The Hague Peace Conferences, the Bretton Woods Conference and the United Nations Conference on the Law of the Sea III, on the development of legislative mechanisms in international law. It underscores the critical role of diplomatic gatherings in shaping norms, codifying principles and establishing institutions that address global challenges while emphasizing their continued relevance in contemporary geopolitics. The study addresses gaps in understanding how inclusivity, flexibility and enforcement mechanisms contribute to the success or failure of international legal frameworks, as well as how unresolved historical legacies, such as the Kurdish question, can be addressed through inclusive diplomacy. Employing a qualitative case study approach, the research analyzes primary and secondary sources from key historical conferences (The Hague, Bretton Woods, UNCLOS III) and recent diplomatic efforts, including climate summits and AI governance initiatives. Drawing on these historical insights, the study also analyzes contemporary diplomatic efforts, such as global climate summits and initiatives addressing the Kurdish question, to explore how modern conferences can address unresolved legacies and emerging challenges. The findings confirm the validity of international regime theory in explaining how diplomatic conferences create lasting legal structures that guide state behaviour. The findings also reveal that successful regimes are built on inclusivity, adaptability and robust enforcement mechanisms, with lessons from past conferences offering valuable insights for addressing modern geopolitical and humanitarian issues.